A few simple facts for the friends of the Negro - Church Missionary Society; Ladies' Society for Promoting the Early Education and Improvement of the Children of Negroes and of People of Colour in the British West Indies; University of Birmingham Library; Adam Matthew Digital (Adam Matthew Digital, 1828)
A presentation of statistics relating to converts and potential converts amongst slaves in Jamaica, prepared by the Church Missionary Society and the Ladies' Society